2002
DOI: 10.1207/s15324796abm2401_06
|View full text |Cite
|
Sign up to set email alerts
|

Measuring spiritual well-being in people with cancer: The functional assessment of chronic illness therapy—spiritual well-being scale (FACIT-Sp)

Abstract: A significant relation between religion and better health has been demonstrated in a variety of healthy and patient populations. In the past several years, there has been a focus on the role of spirituality, as distinctfrom religion, in health promotion and coping with illness. Despite the growing interest, there remains a dearth of well-validated, psychometrically sound instruments to measure aspects of spirituality. In this article we report on the development and testing of a measure of spiritual well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
1,210
8
42

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,370 publications
(1,332 citation statements)
references
References 28 publications
47
1,210
8
42
Order By: Relevance
“…Some 20 scales were identified that measured meaning: the Chinese Cancer Coherence Scale (CCCS) (Chan et al, 2007); the Constructed Meaning Scale (Fife, 1995); the meaning/peace subscale of the Functional Assessment of Chronic Illness Therapy -Spiritual Well-Being Scale (FACIT-Sp) (Canada et al, 2008;Murphy et al, 2010;Peterman et al, 2002); the Illness Cognitions Questionnaire (ICQ) (Evers et al, 2001); the Internal Coherence Scale (ICS) (Kroz et al, 2009); the Life Attitude Profile (LAP)/ Life Attitude Profile -Revised (LAP -R) (Reker, 1992;Reker & Peacock, 1981); the Life Evaluation Questionnaire (LEQ) (Salmon et al, 1996); the Meaning in Life questions (including the Benefit Finding Scale [BFS]) used by Tomich and Helgeson (2002); the Meaning in Life Questionnaire (MLQ) (Steger et al, 2006); the Meaning in Life Scale (MILS) (Jim et al, 2006); the Meaning in Suffering Test (MIST) (Starck, 1983); the Perceived Meanings of Cancer Pain Inventory (PMCPI) (Chen, 1999); the Personal Meaning Profile (PMP) (Wong, 1998); the Positive Meaning and Vulnerability Scale (Bower et al, 2005); the Purpose in Life (PIL) Test (Crumbaugh & Maholick, 1964); the Purposelessness, Understimulation, and Boredom (PUB) Scale (Passik et al, 2003); the Schedule for Meaning in Life Evaluation (SMiLE) (Fegg et al, 2008); the Sense of Coherence (SOC) Scale (Antonovsky, 1993); the Sources of Meaning Profile (SOMP)/Sources of Meaning Profile -Revised (SOMP -R) (Reker, 1996); and the World Assumptions Scale (Janoff-Bulman, 1989). The optimal measure of meaning will vary depending on the purpose and context of the assessment.…”
Section: Meaningmentioning
confidence: 99%
“…Some 20 scales were identified that measured meaning: the Chinese Cancer Coherence Scale (CCCS) (Chan et al, 2007); the Constructed Meaning Scale (Fife, 1995); the meaning/peace subscale of the Functional Assessment of Chronic Illness Therapy -Spiritual Well-Being Scale (FACIT-Sp) (Canada et al, 2008;Murphy et al, 2010;Peterman et al, 2002); the Illness Cognitions Questionnaire (ICQ) (Evers et al, 2001); the Internal Coherence Scale (ICS) (Kroz et al, 2009); the Life Attitude Profile (LAP)/ Life Attitude Profile -Revised (LAP -R) (Reker, 1992;Reker & Peacock, 1981); the Life Evaluation Questionnaire (LEQ) (Salmon et al, 1996); the Meaning in Life questions (including the Benefit Finding Scale [BFS]) used by Tomich and Helgeson (2002); the Meaning in Life Questionnaire (MLQ) (Steger et al, 2006); the Meaning in Life Scale (MILS) (Jim et al, 2006); the Meaning in Suffering Test (MIST) (Starck, 1983); the Perceived Meanings of Cancer Pain Inventory (PMCPI) (Chen, 1999); the Personal Meaning Profile (PMP) (Wong, 1998); the Positive Meaning and Vulnerability Scale (Bower et al, 2005); the Purpose in Life (PIL) Test (Crumbaugh & Maholick, 1964); the Purposelessness, Understimulation, and Boredom (PUB) Scale (Passik et al, 2003); the Schedule for Meaning in Life Evaluation (SMiLE) (Fegg et al, 2008); the Sense of Coherence (SOC) Scale (Antonovsky, 1993); the Sources of Meaning Profile (SOMP)/Sources of Meaning Profile -Revised (SOMP -R) (Reker, 1996); and the World Assumptions Scale (Janoff-Bulman, 1989). The optimal measure of meaning will vary depending on the purpose and context of the assessment.…”
Section: Meaningmentioning
confidence: 99%
“…The questionnaires used to measure patient QoL were the Functional Assessment of Cancer Therapy -Bone Marrow Transplantation scale (FACT-BMT), version 4 (Cella et al, 1993;McQuellon et al, 1997) and the Functional Assessment of Chronic Illness Therapy -the Spiritual Well-being scale (FACITSp), version 4 (Peterman et al, 2002) (Appendix I). The FACIT measurement system is a collection of QoL questionnaires with a core questionnaire, Functional Assessment of Cancer Therapy -General (FACT-G), with a number of supplementary subscales specific to tumour type, treatment or condition.…”
Section: Questionnairesmentioning
confidence: 99%
“…All 23 items in this subscale were included in the questionnaire administered to the patients, but for scoring and analysis the subscale was limited to 10 of the items in accordance with the FACIT guidelines (Cella, 1997). The FACIT-Sp, which is an optional subscale, assesses the patients' spiritual well-being, and comprises 12 items (Peterman et al, 2002). It includes items that deal with sense of meaning and peace and the role of faith in illness, and it produces a total score for spiritual well-being.…”
Section: Questionnairesmentioning
confidence: 99%
See 2 more Smart Citations